Astral microtubules are not required for anaphase B in Saccharomyces cerevisiae (The Rockefeller University Press, 1992)
tub2-401 is a cold-sensitive allele of TUB2, the sole gene encoding beta-tubulin in the yeast, Saccharomyces cerevisiae. At 18 degrees C, tub2-401 cells are able to assemble spindle microtubules but lack astral microtubules. Under these conditions, movement of the spindle to the bud neck is blocked. However, spindle elongation and chromosome separation are unimpeded and occur entirely within the mother cell. Subsequent cytokinesis produces one cell with two nuclei and one cell without a nucleus. The anucleate daughter can not bud. The binucleate daughter proceeds through another cell cycle to produce a cell with four nuclei and another anucleate cell. With additional time in the cold, the number of nuclei in the nucleated cells continues to increase and the percentage of anucleate cells in the population rises. The results indicate that astral microtubules are needed to position the spindle in the bud neck but are not required for spindle elongation at anaphase B. In addition, cell cycle progression does not depend on the location or orientation of the spindle.